A case report of symptomatic gallbladder disease in the setting of peritoneal carcinomatosis originating from invasive lobular carcinoma of the breast. (2016) - Brinkman, David; Misra, Subhasis; Aydin, Nail
Highlights: Gallbladder disease in peritoneal carcinomatosis from invasive lobular carcinoma. Preferred initial evaluation for these patients is a diagnostic laparoscopy. Portal involvement of carcinomatosis is a major concern. A laparoscopic cholecystectomy can be undertaken selectively. Treatment is dependent on laparoscopic findings and surgeon experience. Abstract: Introduction: Invasive lobular carcinoma is the second most common type of breast cancer, responsible for 5–15 percent of all cases. Peritoneal carcinomatosis secondary to breast cancer is a rare event, frequently resulting in morbidity and mortality. Symptomatic gallbladder disease in the setting of peritoneal carcinomatosis originating from invasive lobular carcinoma of the breast is a very rare event and is not well covered in literature. Presentation of case: A 44 year old female patient previously diagnosed with stage IV invasive lobular carcinoma of the left breast with widespread systemic metastases and peritoneal carcinomatosis presented with a three week history of right upper quadrant pain trigged by food intake only, greatly diminishing her quality of life. She had spent almost a year in a progression free disease status but was now suffering from debilitating symptomatic gallbladder disease. Despite the extent of her peritoneal carcinomatosis, she elected to undergo a laparoscopic cholecystectomy. Discussion: We are presenting a rare case of symptomatic gallbladder disease in the setting of peritoneal carcinomatosis secondary to invasive lobular carcinoma. A major concern is tumor load within nearby portal structures. Even though laparoscopic cholecystectomy could be a viable option to treat the condition, it needs to be applied selectively and very cautiously in the respective patient population. Conclusion: Symptomatic gallbladder disease in the setting of peritoneal carcinomatosis secondary to invasive lobular carcinoma is an uncommon presentation to surgeons. A diagnostic laparoscopy is the preferred initial evaluation. If deemed feasible, and if the surgeon has the required experience, a laparoscopic cholecystectomy can be undertaken selectively.